A Qard-Based Microfinance under PNM Mekaar Syariah: A Legal Assessment from the Perspective of Positive Sharia Law and Classical Islamic Jurisprudence - Novianti, Vira Dwi (Jurnal Syariah dan Hukum Komparatif, 2025)
Qard contract, or benevolent loan, is widely recognized in Islamic finance as a non-interest-based instrument aimed at promoting social welfare. PNM Mekaar Syariah utilizes qard-based microfinance to empower women entrepreneurs in Indonesia. This study assesses the legal basis and implementation of qard within this program from the perspectives of positive Sharia law and classical Islamic jurisprudence. This research employs normative legal analysis using primary legal sources, including DSN-MUI fatwas, national regulations, and classical fiqh texts. A comparative approach is used to evaluate convergence and divergence between modern legal frameworks and traditional Islamic thought. Findings reveal substantial alignment between both perspectives regarding the permissibility and objectives of qard. However, divergences emerge in the treatment of administrative fees, group liability, and repayment terms. Classical jurists emphasize the non-commercial, voluntary nature of qard, while positive Sharia law permits institutional adaptations under regulatory oversight. The study highlights the need for policy reforms to harmonize institutional practices with classical ethical principles, especially concerning borrower protection and contract purity. Qard-based microfinance under PNM Mekaar Syariah is legally and ethically viable when guided by maqāṣid al-sharīʿah and strengthened through consistent Sharia governance.